2014
DOI: 10.4236/ajps.2014.515237
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Various Row Spacing on the Yield and Yield Components of Raya Anmol and Faisal Canola under Coastal Climatic Conditions of Lasbela

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
2
1
1
Order By: Relevance
“…However, there were no row spacing effects on spring wheat and winter wheat in Saskatchewan, Canada (Lafond and Gan, 1999;Johnston and Stevenson, 2001) and in the North China Plain (Chen et al, 2010). While most studies found that canola yield was higher for narrower row spacing in different regions (Kutcher et al, 2013;Liu et al, 2014), a higher canola yield was also observed for wider row spacing under coastal climatic conditions of Lasbela (Waseem et al, 2014). Therefore, row spacing effects may depend on specific climatic conditions of an area, and yield component compensation may contribute to non-decreasing crop yields with wider row spacing in some regions.…”
Section: Introductioncontrasting
confidence: 45%
“…However, there were no row spacing effects on spring wheat and winter wheat in Saskatchewan, Canada (Lafond and Gan, 1999;Johnston and Stevenson, 2001) and in the North China Plain (Chen et al, 2010). While most studies found that canola yield was higher for narrower row spacing in different regions (Kutcher et al, 2013;Liu et al, 2014), a higher canola yield was also observed for wider row spacing under coastal climatic conditions of Lasbela (Waseem et al, 2014). Therefore, row spacing effects may depend on specific climatic conditions of an area, and yield component compensation may contribute to non-decreasing crop yields with wider row spacing in some regions.…”
Section: Introductioncontrasting
confidence: 45%
“…El efecto genotípico sobre la densidad de población en canola ha sido analizado en muchos estudios, en donde las diferencias en rendimiento de semilla han sido mínimas (Różyło y Pałys, 2014), mientras que otros mencionan que las diferencias en rendimiento pueden estar dadas por la diferente estructura de la planta (Waseem et al, 2014). En este sentido nuestros datos muestran que Hyola 61 fue estadísticamente superior (14%), a Bioaureo 2486 en índice de cosecha, mientras que Bioaureo 2486 fue estadísticamente superior en producción biomasa (18%), peso de 1 000 semillas (3%) y número de ramas (11%) a Hyola 61 (Cuadro 2).…”
Section: Condiciones Climáticasunclassified
“…Morrison et al (1990), Ozer (2003), Yazdifar and Valiollah (2009), Uzun et al (2012) or Wang et al (2015) observed similar results. Waseem et al (2014) reached a different conclusion, i.e. that the highest seed yield was achieved with the widest rows (60 cm).…”
mentioning
confidence: 94%